Development planning : the essentials of economic policy - Lewis, W. Arthur (London : Allen & Unwin, 1966)
This book is on how development plan is made, what the chief snags are, and what distinguishes good planning from the bad
Includes bibliographical references and index.
oo 05/09/2018
Loans
Keywords: Economic policy